Salmonella Typhi genomics: envisaging the future of typhoid eradication - Yap, K.P.; Thong, Kwai Lin (Wiley, 2017)
Next-generation whole-genome sequencing has revolutionised the study of infectious diseases in recent years. The availability of genome sequences and its understanding have transformed the field of molecular microbiology, epidemiology, infection treatments and vaccine developments. We review the key findings of the publicly accessible genomes of Salmonella enterica serovar Typhi since the first complete genome to the most recent release of thousands of Salmonella Typhi genomes, which remarkably shape the genomic research of S. Typhi and other pathogens. Important new insights acquired from the genome sequencing of S. Typhi, pertaining to genomic variations, evolution, population structure, antibiotic resistance, virulence, pathogenesis, disease surveillance/investigation and disease control are discussed. As the numbers of sequenced genomes are increasing at an unprecedented rate, fine variations in the gene pool of S. Typhi are captured in high resolution, allowing deeper understanding of the pathogen's evolutionary trends and its pathogenesis, paving the way to bringing us closer to eradication of typhoid through effective vaccine/treatment development.